2016
DOI: 10.1007/s11356-016-7337-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in tissues of scorpionfish (Scorpaena porcus) caught from Black Sea (Turkey) and potential risks to human health

Abstract: Scorpionfish (Scorpaena porcus) is a demersal fish species commercially important for its of which meat is tough and delicious. The aim of this study was to determine heavy metal (Al, Cu, Ni, As, Cd, Hg, Pb, U) concentrations in this fish species which is traditionally consumed in the Black Sea Area and, to compare the concentrations of various toxic elements in different organs of the fish specimens (muscle, liver, gill, and skin). Within this scope, the mineralization was performed using microwave digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 56 publications
1
10
1
Order By: Relevance
“…Since the exposure to two or more toxic metals may result in additive effects [41], the total target hazard quotient (TTHQ) was also calculated as the arithmetic sum of each THQ values [42,43]:TTHQ = THQ Hg + THQ Cd + THQ Pb …”
Section: Methodsmentioning
confidence: 99%
“…Since the exposure to two or more toxic metals may result in additive effects [41], the total target hazard quotient (TTHQ) was also calculated as the arithmetic sum of each THQ values [42,43]:TTHQ = THQ Hg + THQ Cd + THQ Pb …”
Section: Methodsmentioning
confidence: 99%
“…RfD: Oral referans dose (mg/kg/day) (Table 2) AT: Average exposure time for non-carcinogenic effects (365 days/year x ED) ED: Exposure duration (70 years for a person is assumed in this study, equivalent to the average lifetimes), HQ is categorized into six classes: HQ<1 (no health risk); 1<HQ<1.5 (low health risk); 1.5<HQ<2 (medium-low health risk); 2<HQ<2.5 (medium risk); 2.5<HQ<3 (next higher risk); 3<HQ (high risk) (USEPA, 1989;Çulha et al, 2016;Alkan et al, 2020).…”
Section: Target Hazard Quotient (Thq)mentioning
confidence: 99%
“…In fact, variation in physical and chemical characteristics (e.g., pH, salinity, redox potential), natural resuspension phenomena caused by waves, currents and bioturbation and/or and anthropic disturbances, including boat wash, dredging and disposal actions or bottom trawling, can lead to the resuspension of these particle-associated contaminants into the overlying water (Hedman et al 2009;Jonas and Millward 2010;Juwarkar et al 2010). Particle-associated and dissolved contaminants that are suspended or released from contaminated sediments returned as available for the uptake by organisms, either via particle uptake or via transport across biological membranes (e.g., Storelli and Marcotrigiano, 2000;Eggleton and Thomas 2004;Conte et al, 2016;Çulha et al, 2016), representing a serious hazard for the health of living organisms and, potentially, of humans eating contaminated organisms. For instance, field studies have demonstrated that dredging operations of contaminated sediments enhanced the uptake of polycyclic aromatic hydrocarbons (PAHs) and heavy metals (e.g., Bocchetti et al 2008), as well as of polychlorinated biphenyl (PCBs; Bellas et al 2007), in mussel species.…”
Section: Introductionmentioning
confidence: 99%